An Exploration of Factor Affecting Household’s Travel Cost Budget Considering Household Life Stages Applying to Urban Bus Ridership - Sugiarto Sugiarto; Lulusi Lulusi; Cut Mutiawati; Sofyan M. Saleh; Qurrata A'yuni; Irham Iskandar (Aceh International Journal of Science and Technology, 2020)
Urban bus reform so-called Trans Koetaradja (TK) is regarded as a potential urban transport policy aiming at alleviating autos traffic congestion and mitigating highly private mode dependency in Banda Aceh, Indonesia. The new bus system proposed by the Government has been operated since early 2018, and it remains free of fare services due to subsidy provide by the Government as the bus corridors have been expanded the budget getting escalating year by year. To reduce the burden of subsidies, the Government intends to drop monetary aid by applying full fare for the bus. However, declining the subsidy could affect bus ridership, especially low-income households whose captive riders may not afford the ticket. It hypothesizes that the travel cost budget (TCB) has significantly influenced the ability to pay for a particular household to afford the bus fare. The TCB for this study defines the maximum amount of money allocated by a specific family for their transportation within a month. Therefore, this study is aiming at exploring factors that effecting the households' transportation expenditures, taking into account household life stages (HLS) among TK' bus users. The use of revealed preference data obtained in 2019, the regression analysis of the ordinary least square (OLS) method, was used to calibrate and teste the exogenous variables across HLS. To simplify, the HLS in this study is segmented as early, middle, and established HLS. The distribution of TCB across HLS revealed that the share of transport expenditure on average to their monthly income had shared about 10-11 %. The finding from the OLS indicates that the variables of the female gender, monthly income, and the number of owned motorcycles have significant contributions to the TCB. The most significant finding is the impact of monthly income on the TCB across HLS. It exhibited early, and middle HLS has shown more spending share on income compared to the established HLS